Efektivitas Media Pembelajaran Quiz Wordwall untuk Meningkatkan Kemampuan Menulis Nilai Mata Uang Bagi Anak Tunagrahita Ringan - Simanjuntak, Riris; Budi, Setia; Iswari, Mega; Zulmiyetri, Zulmiyetri; Zulpiani, Mardhatillah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to improve the ability to write currency values in mildly mentally retarded children at SLB N 1 Lubuk Sikaping by using wordwall quizzes learning media, namely website-based quizzes that enable the creation of interactive learning. With this media, teachers can create various types of learning such as quizzes, pair matching, random word games, word searches, and grouping. This research uses an experimental method with a single subject research (SSR) approach and an A-B-A design, involving three conditions: baseline (A1), intervention (B), and baseline (A2). Data was collected through observations and tests which were analyzed based on two categories, namely analysis within conditions and visual analysis between conditions. During 16 meetings, the research results showed that in the baseline condition (A1) which consisted of 4 meetings, the percentage of child stability was only 14%. However, in the intervention condition (B) which consisted of 8 meetings, stability was achieved at the 9th to 12th meeting with a percentage reaching 100%. In the baseline condition (A2), which also consists of 4 meetings, the stable percentage remains 100%. Based on these results, it can be concluded that the use of wordwall quiz media is effective in improving the ability to write currency values in mildly mentally retarded children